Investigating the use of 3D printed soft magnetic PEEK‐based composite for space compliant electrical motors. Issue 20 (17th January 2022) - Ferrara, Miriam; Rinaldi, Marianna; Pigliaru, Lucia; Cecchini, Federico; Nanni, Francesca
Abstract: Electric motors are ubiquitous on spacecraft and their smooth operation relies on the presence of naturally magnetic materials. The employment of conventional metal‐based magnets causes some inconveniences such as high values of specific gravity and the limited reproducibility of complicated geometries. The introduction of novel polymer‐based magnetic materials processed via additive manufacturing represents a brilliant answer to these needs. This paper describes the first‐time development of a polyether ether ketone‐magnetite (Fe3 O4 ) soft magnetic composite. The material was prepared by adding 50 wt% magnetic microparticles to the polymeric matrix. The composite material was extruded in form of filaments and 3D printed via fused filament fabrication. The thermomechanical characterization demonstrated the stability of the material at both processing ad use temperatures, while the magnetic analysis reported a typical soft magnetic behavior with 25.7 A m 2 kg −1 magnetization at saturation. The measured properties were employed as inputs for the finite element analysis of an axial flux brushless direct current electric motor, as a proof of concept. The simulation of the electromechanical behavior of the motor showed promising performance for the composite material, reaching the maximum deliverable torque of about 0.8 Nm (compliant to small power aerospace applications such as micro‐actuators and mini control moment gyroscopes) with weight savings up to 50%. Abstract :